A State-of-the-art Review on Micro Electro-discharge Machining. (2016) - Raju, Leera; Hiremath, Somashekhar S.
Abstract: Electro-Discharge Machining (EDM) is one of the non-conventional machining processes available, in which the material removal takes place due to melting and vaporisation of electrode materials. Micro Electro-Discharge Machining (μ-EDM) is a variant of EDM, is playing an important role in generation of micro features on difficult to machine conducting materials. In this paper, authors carried out an extensive literature study to give a complete description on μ-EDM process, its requirements, performance and applications. More than fifty papers were referred and the details were categorized into five major areas, namely, experimental setups and its subsystems, experimental studies and optimization methods, generated micro features, modeling and simulation approaches and applications.